ESTIMASI OUTPUT BERBAGAI BANGSA KAMBING DI DESA DADAPAN KECAMATAN SUMBEREJO KABUPATEN TANGGAMUS - Hasri, Lara Permataning; Suharyati, Sri; Sulastri, Sulastri (JURUSAN PETERNAKAN, FAKULTAS PERTANIAN, UNIVERSITAS LAMPUNG, 2018)
This study aims to determine the value of Natural Increase (NI), Net Replacement Rate (NRR), and output on each goat nation in Dadapan Village Sumberejo District Tanggamus. This research was conducted from June to August 2017. The research was conducted by survey method to all goat and goat breeders in Dadapan Village. Research results show the value of NI goat Saburai 26.24%, male and female NRR value of 756.23% and 192.27%, Output 27.66% (36 tail). Boerawa goats NI value 11.32%, male and female NRR 191,81% and 125,71%, Output 15,72% (20 tail). NI Rambon goats 24.22%, male and female NRR 636.21% and 134.19%, Output 27.33% (42 tail). NI goat PE 19.53%, male and female NRR 264.53% and 143.99%, Output 20.31% (12 tail). The goats that have the potential to be developed in Dadapan Village are Saburai goats Key words: Natural Increase, Net Replacement Rate, Output breeds of goat